Glazialmorphologische und dendrochronologische Untersuchungen neuzeitlicher Eisrandlagen Ost- und Südtibets - Bräuning, Achim; Lehmkuhl, Frank (ERDKUNDE, 1996)
Investigations of glacier forefields at two sites in eastern and southern Tibet (Chola Shan and Nyainqentanglha Shan, see Fig. 1), show four different ice margins of recent glaciation (I to IV) and one older glacial stage (V). The poor weathering and sharp relief of the moraines, together with the low degree of soil development and vegetation cover, allow the younger phases (I to IV) to be assigned to the global event of the Little Ice Age. Similar moraines, with only sparse vegetation, can also be observed in other regions of the Tibetan plateau. The moraine ridges I to III are retreat phases of the maximum advance IV and can be dated by dendrochronology to the end of the 19th and early 20th century. A minimum age far stage IV is 1788. Phases with reduced tree growth can be correlated with cooler summer conditions and, to some extent, with enhanced glacier activity. The Little Ice Age event coincides with cooling periods in China and Tibet in the 14th to 19th century. In the Nianbaoyeze (eastern Tibet), a fossil soil with a radiocarbon age of 1385:t 170 BP indicates a maximum age far stage IV. The older, densely vegetated moraine stage V might correspond to the so called Neoglacial period beginning about 3000 BP.